2013
DOI: 10.3389/fnhum.2013.00641
|View full text |Cite
|
Sign up to set email alerts
|

Emotional modulation of the attentional blink and the relation to interpersonal reactivity

Abstract: The extent of the attentional blink effect on detection rates in rapid serial visual presentations is modulated by the emotionality of the stimuli. Emotionally salient stimuli are detected more often, even if presented in the attentional blink period, and elicit an enlarged P3 response, which has been interpreted as enhanced consolidation. This effect correlates with individual differences in trait affectivity such as anxiety or dysphoria. Here, we ask if it is also related to the capacity to detect emotions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
1
18
1
Order By: Relevance
“…Using a very similar methodology, but presenting neutral subliminal adjectives, none of the subjects were excluded in a previous study (Jiménez-Ortega et al, 2014 ). A major explanatory factor could therefore be the emotional nature of the subliminal adjectives in the present study, in consonance with recent studies in which enhanced detection is reported for emotional stimuli in attentional blink paradigms (Kanske et al, 2013 ). Our data support this possibility, although in our case the effect seems mainly supported by positive adjectives, since the analyses revealed that these adjectives were significantly easier to detect (see “Results” Section for details).…”
Section: Discussionsupporting
confidence: 90%
“…Using a very similar methodology, but presenting neutral subliminal adjectives, none of the subjects were excluded in a previous study (Jiménez-Ortega et al, 2014 ). A major explanatory factor could therefore be the emotional nature of the subliminal adjectives in the present study, in consonance with recent studies in which enhanced detection is reported for emotional stimuli in attentional blink paradigms (Kanske et al, 2013 ). Our data support this possibility, although in our case the effect seems mainly supported by positive adjectives, since the analyses revealed that these adjectives were significantly easier to detect (see “Results” Section for details).…”
Section: Discussionsupporting
confidence: 90%
“…It is interesting that the findings of this study are less consistent with results obtained by Kanske, Schönfelder, and Wessa (2013). They conducted an experiment measuring both behavior and ERP using an AB paradigm similar to our study.…”
Section: Discussioncontrasting
confidence: 80%
“…4, Table 3). This analysis indeed yielded distinct 606 networks that resembled the task-based networks (Table S11) Perry et al, 2010) and that 807 inter-individual differences in perspective taking correlate with early 808 emotion detection (Kanske et al, 2013b). Because the EmpaToM as- …”
mentioning
confidence: 88%